The Kindlin-2 regulation of epithelial-to-mesenchymal transition in breast cancer metastasis is mediated through miR-200b - Khalid Sossey-Alaoui (Nature Portfolio, 2018)
Abstract Metastasis is the main cause of death in cancer patients, including breast cancer (BC). Despite recent progress in understanding the biological and molecular determinants of BC metastasis, effective therapeutic treatments are yet to be developed. Among the multitude of molecular mechanisms that regulate cancer metastasis, the epithelial-to-mesenchymal transition (EMT) program plays a key role in the activation of the biological steps leading to the metastatic phenotype. Kindlin-2 has been associated with the pathogenesis of several types of cancers, including BC. The role of Kindlin-2 in the regulation of BC metastasis, and to a lesser extent in EMT is not well understood. In this study, we show that Kindlin-2 is closely associated with the development of the metastatic phenotype in BC. We report that knockout of Kindlin-2 in either human or mouse BC cells, significantly inhibits metastasis in both human and mouse models of BC metastasis. We also report that the Kindlin-2-mediated inhibition of metastasis is the result of inhibition of expression of key molecular markers of the EMT program. Mechanistically, we show that miR-200b, a master regulator of EMT, directly targets and inhibits the expression of Kindlin-2, leading to the subsequent inhibition of EMT and metastasis. Together, our data support the targeting of Kindlin-2 as a therapeutic strategy against BC metastasis.